A case study on the treatment of protein SIRAS data. (1st October 2014) - Yao, Deqiang; Zhang, Tao; He, Yao; Han, Pu; Cherney, Maia; Gu, Yuanxin; Cygler, Miroslaw; Fan, Haifu
<x xml:space="preserve">Abstract</x> A case study has been made on the treatment of the SIRAS (single isomorphous replacement with anomalous scattering) data of the originally unknown protein LegC3N. An alternative treatment has been proposed which led to improved results in this particular test case. The treatment involves iterative direct‐method SAD (single‐wavelength anomalous diffraction) phasing and direct‐method‐aided model completion, both of which are implanted in the IPCAS (Iterative Protein Crystal‐structure Automatic Solution) pipeline. Apart from the experimental data, a simulated SIRAS data set for LegC3N with the derivative data truncated to 5.0 Å resolution has also been tested. SAD phasing and phase/model extension in PHENIX without direct methods failed to solve the structure using these simulated SIRAS data. However, the procedure proposed here involving direct methods in both SAD phasing and phase/model extension led to a nearly complete structure model. This shows the potential ability of treating SIRAS data with a derivative diffracting to lower resolution.